A novel surgical procedure for papilla reconstruction using platelet rich fibrin - Lalitha Tanjore Arunachalam; Satyanarayana Merugu; Uma Sudhakar (Wolters Kluwer Medknow Publications, 2012)
Loss of interdental papilla predisposes to phonetic, functional, and esthetic problem. Surgical techniques are manifold, but are challenging and very unpredictable. The purpose of this case report is to present the use of platelet rich fibrin (PRF) in the reconstruction of papilla in the maxiallry anterior region of a forty year old woman who presented with loss of interdental papillae in 11, 12 and 11, 21 region. PRF was tucked in to the pouch created with a semilunar pedicle flap and the entire gingivopapillary unit was displaced coronally. Optimal fill was noted at 3 and 6 months postoperatively. Use of PRF may thus be the panacea for interdental papilla augmentation.